Study on the quality of worklife towards employees work engagement at Gerik district council, Gerik, Perak. / Rafidah Mohamad Shaubi - Mohamad Shaubi, Rafidah (Faculty Of Business Management, Universiti Teknologi MARA, Pahang, 2016)
The purpose of this study was to investigate the quality of work life towards employees work engagement at Gerik District Council. The scope for the research was the permanent employees at Gerik District Council and about 40 respondents involved in answering the questionnaire. Correlational research was the type of research that had been choosen, it was because this research described about the relationship between qualities of work life towards employee work engagement. Then, the data was successfully gathered from the distribution of questionnaire to 40 respondents of Gerik District Council (MDG). After that, the data analysis was arranged according to each variable. The data of the study were successfully gathered through the distribution of questionnaires and used simple random sampling to make sure each employee's in every department at different age, gender or status get the same question. For the research study, the data collected were analyzed by using the Statistical Package for Social Science (SPSS) software version 18.0. The result identified that there are very strong relationships for correlation coefficient with the life and total space towards work engagement. The other was adequate and fair compensation, opportunity for continues growth and security, and the last factor is safe and healthy working condition. As employer, they play important roles to find out factors to increase employee work performance by communication or through effective training to the employees.